PENGARUH PEMBERIAN JUS BUAH BELIMBING WULUH TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DIWILAYAH KERJA PUSKESMAS TELAGA - Fadli Syamsuddin; Nikmawati Puluhulawa; Nun Ain Pango (Universitas Muhammadiyah Gorontalo, 2019)
Hypertension is a situation where an increase of blood pressure is above the normal threshold, systole> 140 mmHg and diastole> 90 mmHg. Wuluh starfruit juice is one of the health therapies to reduce blood pressure in patients with hypertension. The aim of this study was to determine the effect of giving wuluh starfruit juice to reduce blood pressure in people with hypertension. The researcher used Quasy Experiment with One Group Pretest-Posttest design. The respondents were 20 people with hypertension. The respondents in experimental group were given 200 ml wuluh starfruit juice once in 5 days in a row. The results of this study showed a decrease in blood pressure where the data analysed by using the Wilcoxon statistical test results and it obtained a P value = 0.000 (α <0.05). It can be inferred that there is an effect of giving starfruit juice to a decrease blood pressure. So it is recommended to people with hypertension to consume wuluh starfruit as an alternative medication for hypertension.